2005
DOI: 10.1152/ajpcell.00636.2004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the COOH terminus of human presenilin 1 is located in extracytoplasmic space

Abstract: The polytopic membrane protein presenilin 1 (PS1) is a component of the γ-secretase complex that is responsible for the intramembranous cleavage of a number of type I transmembrane proteins including the β-amyloid precursor protein (APP). Mutations of PS1, apparently leading to aberrant processing of APP, have been genetically linked to early-onset familial Alzheimer's disease. PS1 contains ten hydrophobic regions (HRs) sufficiently long to be α-helical membrane spanning segments. Most topology models for PS1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
3
15
0
Order By: Relevance
“…The ER-retention signal of PS1 is probably embedded in the membrane, as a number of groups recently showed that the hydrophobic part of the PS1 C-terminus spans the membrane. This suggests a topology with nine TMDs for PS [8][9][10] . In the case of PEN-2, the retention/retrieval signal is located in TMD1 and involves a critical asparagine [Kaether et al, submitted].…”
Section: Assembly Of the ␥ -Secretase Complexmentioning
confidence: 89%
See 1 more Smart Citation
“…The ER-retention signal of PS1 is probably embedded in the membrane, as a number of groups recently showed that the hydrophobic part of the PS1 C-terminus spans the membrane. This suggests a topology with nine TMDs for PS [8][9][10] . In the case of PEN-2, the retention/retrieval signal is located in TMD1 and involves a critical asparagine [Kaether et al, submitted].…”
Section: Assembly Of the ␥ -Secretase Complexmentioning
confidence: 89%
“…The responsible genes, termed presenilin 1 (PS1) and presenilin 2 (PS2) were predicted to encode two homologous ϳ 50-kDa polytopic membrane proteins, that according to recent models consist of 9 transmembrane domains (TMDs) [8][9][10] . Both are endoproteolytically cleaved between TMDs 6 and 7 into an N-terminal and C-terminal fragment (NTF, CTF) [11] .…”
Section: Identification Of ␥ -Secretasementioning
confidence: 99%
“…Recently, however, several cell-based topological studies revealed that the hydrophobic region 9 (I408 -F428) and 10 (A434 -V453) of PS1 (Henricson et al, 2005) penetrate the membrane as TMD8 and TMD9, respectively, and that the extreme C terminus is exposed to the extracellular/luminal side (Laudon et al, 2005;Oh and Turner, 2005;Spasic et al, 2006). Moreover, the PAL motif that resides at the N-terminal region of the hydrophobic region 10 is highly conserved in PS and SPP proteins and is required for the enzymatic activity (Tomita et al, 2001;Wang et al, 2004;Nakaya et al, 2005;J.…”
Section: Scam Analysis Of Hydrophobic Region 9 and The Pal Motif Of Ps1mentioning
confidence: 99%
“…The active site aspartate residues are displayed in red. PS is depicted according to the recent nine TMD model (Henricson et al, 2005;Laudon et al, 2005;Oh and Turner, 2005).…”
Section: Ps1/spe-4 6/7 Is Deficient In Notch Signalingmentioning
confidence: 99%